2023
DOI: 10.3389/fnut.2023.1104925
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary habits and incident thyroid cancer: A prospective cohort study

Abstract: BackgroundIn addition to the thyroid cancer (TC) risk from lifestyle and environmental factors such as radiation exposure, some studies have indicated that diet may affect TC development; however, previous findings are inconsistent. The objective of our study was to investigate the association between dietary habits and TC risk in a Korean population.Materials and methodsA total of 13,973 participants were selected after excluding ineligible subjects from the Cancer Screenee Cohort at National Cancer Center in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…However, a Japanese cohort study and an Italian case-control study have suggested that individuals with higher dairy intake had a lower TC risk [30,32]. A recent National Cancer Center survey in Korea discovered that consuming milk and dairy products more than 5 times/week is associated with a reduced risk of TC [8]. Our study identified a reverse J-shaped relationship with dairy consumption, aligning with previous research and showing an increased TC risk when consuming too few dairy products.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…However, a Japanese cohort study and an Italian case-control study have suggested that individuals with higher dairy intake had a lower TC risk [30,32]. A recent National Cancer Center survey in Korea discovered that consuming milk and dairy products more than 5 times/week is associated with a reduced risk of TC [8]. Our study identified a reverse J-shaped relationship with dairy consumption, aligning with previous research and showing an increased TC risk when consuming too few dairy products.…”
Section: Discussionsupporting
confidence: 89%
“…Our study comprehensively evaluated 106 food items, including 337 foods that majorly contribute to 17 nutrients, including seasonal items, and was conducted by trained interviewers. In contrast, a prior National Cancer Center study utilized a dietary habit questionnaire consisting of only 12 items, potentially lacking a comprehensive assessment of all food items influencing TC development [8]. Confirmation of our findings will necessitate future studies, and investigating and considering specific dairy products, such as milk and butter, in more detail is essential.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations